Sorption and Fate of Perchlorate in Arid Soils - Escudey-Castro, A; Escudey-Castro, A (Taylor and Francis Ltd., 2016)
The mobility of perchlorate in soils depends on several factors, including soil mineralogy and the presence of other oxyanions that compete with perchlorate for the retention sites. Currently, there are no studies that evaluate the mobility of perchlorate in arid soils. The present study evaluated the mobility of ClO4– in three arid soils, Canchones, Humberstone and Pica, exposed to two ClO4– concentration ranges and different ionic strengths. In Humberstone (non-agricultural) and Pica (agricultural) soils, the sorption processes were not important for both concentration ranges, while Canchones soil (agricultural) showed a decrease in perchlorate concentration associated with microbial degradation processes. The increase of medium ionic strength by addition of Ca(NO3)2 only had an important effect on Humberstone soil, associated with the presence of kaolinite and muscovite (variable charge). A competition effect was observed between perchlorate, nitrate and other anions presents in solution by absorption sites generated from variable charge mineral and calcium. Considering the quite low sorption capacity of the soils and the high solubility, perchlorate can be absorbed by fruit and vegetables of export in concentrations over the healthy levels established by international organization. © 2016 Taylor & Francis.